The effect of working capital on profitability of poultry egg enterprise in Osun State, Nigeria - Kehinde, Ayodeji (Applied Studies in Agribusiness and Commerce, 2022)
This study investigated the effect of working capital on the profitability of poultry egg enterprise.   Primary data were collected from 180 poultry egg farmers using two-stage sampling technique. Data were collected on the socio-economic characteristics such as age, gender, educational qualification, farming experience and flock size owned, quantities of inputs and outputs. Descriptive statistics, farm budgetary technique and ordinary least square model were used to analyze the data collected.  The results from descriptive statistics show mean values of 42 years, 9 years and 5 persons for age, years of experience and household size, respectively. Majority of poultry egg farmers (52.2%) used their personal savings to fund their businesses while, some had access to loan from co-operative societies (37.2%), from SEAP microfinance (6.7%) and from banks (3.9%). Poultry egg producers invested their working capital on feeds (64.8%), rearing of poultry birds from day old chicks to point of lay (14.8%), account receivables (13.6%), drugs & vaccines (2.4%) and variable overheads (4.4%). A total cost of ₦5,494,927.04k was incurred by the poultry egg producers. Cost of feed accounted for 71.89% of the total cost of production. A total revenue of ₦9,388,555.60k and the net returns of ₦3,893,628.56k were realized. The net farm income per bird from the enterprise was ₦1,698.05k while the gross margin per bird was ₦1,795.32. The ordinary least squares regression estimates revealed that inventory, account receivable, operating cycle and flock size have significant effect on the profitability of poultry egg enterprises. The study concluded that poultry egg enterprise is profitable and working capital has a significant effect on the profitability of poultry egg enterprise. In light of the findings, the study recommended the expansion of the poultry flock size as well as reduction in the number of days of inventories, account receivables and operating cycle in order to increase the profitability of poultry egg enterprise.